2017
DOI: 10.18632/oncotarget.22770
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a inhibits cells proliferation and invasion by downregulating Notch1 in endometrial cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs composed of 18-25 nucleotides that regulate the expression of approximately 30% of human protein coding genes. Dysregulation of miRNAs plays a pivotal role in the initiation and progression of malignancies. Our study has shown that microRNA-34a (miR-34a) was upregulated in human endometrial cancer stem cells (ECSCs). However, it is unknown how miR-34a regulates endometrial cancer itself. Here, we report that miR-34a directly and functionally targeted Notch1. MiR-34a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
(27 reference statements)
2
28
0
Order By: Relevance
“…Of the four discriminating miRNAs between EEC and SEC identified in this study, only miR-34a-5p has been studied extensively. In non-selective EC, a decreased miR-34a-5p level was reported to associate with higher stage and metastasis [ 43 , 44 ], whereas another study revealed that miR-34a-5p targets SNAIL and other genes such as those involved in epithelial-mesenchymal transition (EMT) [ 45 ]. In another study, decreased miR-34a-5p expression upregulated the L1CAM level in EC cell lines and tumours [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the four discriminating miRNAs between EEC and SEC identified in this study, only miR-34a-5p has been studied extensively. In non-selective EC, a decreased miR-34a-5p level was reported to associate with higher stage and metastasis [ 43 , 44 ], whereas another study revealed that miR-34a-5p targets SNAIL and other genes such as those involved in epithelial-mesenchymal transition (EMT) [ 45 ]. In another study, decreased miR-34a-5p expression upregulated the L1CAM level in EC cell lines and tumours [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-34a and miR-424 are reduced and thought to be tumor suppressors in EC [ 21 , 22 ]. Consistent with these studies, we found low levels of miR-34a and miR-424 in EC cell lines and EC patient tissues, and these low expressions correlated with a poorer prognosis in EC.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies suggest that miRNAs are closely associated with tumorigenesis. Additionally, miRNAs are demonstrated to regulate tumor cell proliferation, migration and invasion by suppressing target gene expression post-transcriptionally ( 27 ). Abnormal expression of miRNAs is frequently observed in types of cancer, including breast cancer ( 28 ), colorectal cancer ( 29 ), non-small cell lung cancer ( 30 ) and hepatocellular carcinoma ( 31 ).…”
Section: Discussionmentioning
confidence: 99%